Код личного счастья - Рой Олег (Капризы изменчивой судьбы, 2017)
Экземпляры: ф-4 (20180723) / Инвентарный номер: 52339 / Цена: 266.40 / Сис.шифр: Р2 / Авт.знак: Р 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6